2004
DOI: 10.1124/jpet.103.059527
|View full text |Cite
|
Sign up to set email alerts
|

SSR240612 [(2R)-2-[((3R)-3-(1,3-Benzodioxol-5-yl)-3-{[(6-methoxy-2-naphthyl)sulfonyl]amino}propanoyl)amino]-3-(4-{[2R,6S)-2,6-dimethylpiperidinyl]methyl}phenyl)-N-isopropyl-N-methylpropanamide Hydrochloride], a New Nonpeptide Antagonist of the Bradykinin B1Receptor: Biochemical and Pharmacological Characterization

Abstract: The biochemical and pharmacological properties of a novel non-peptide antagonist of the bradykinin (BK) B 1 receptor, SSR240612 [(2R)-2-[((3R)The compound selectivity for B 1 versus B 2 receptors was in the range of 500-to 1000-fold. SSR240612 inhibited Lys 0 -desAr 9 -BK (10 nM)-induced inositol monophosphate formation in human fibroblast MRC5, with an IC 50 of 1.9 nM. It also antagonized des-Arg 9 -BK-induced contractions of isolated rabbit aorta and mesenteric plexus of rat ileum with a pA 2 of 8.9and 9.4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 24 publications
(25 reference statements)
2
65
2
Order By: Relevance
“…Thus, the activation of B 1 receptors is a critical step in the production of neuropathic pain, and B 1 receptor blockade is able to not only prevent the development of nociception but also reduce an established painful condition. phenyl)-N-isopropyl-N-methylpropanamide hydrochloride] was able to reduce the thermal hyperalgesia produced by sciatic nerve injury in rats (Gougat et al, 2004). These findings support the notion that the development of oral-selective B 1 receptor antagonists might be expected to have clinical therapeutic potential in the management of neuropathic pain.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, the activation of B 1 receptors is a critical step in the production of neuropathic pain, and B 1 receptor blockade is able to not only prevent the development of nociception but also reduce an established painful condition. phenyl)-N-isopropyl-N-methylpropanamide hydrochloride] was able to reduce the thermal hyperalgesia produced by sciatic nerve injury in rats (Gougat et al, 2004). These findings support the notion that the development of oral-selective B 1 receptor antagonists might be expected to have clinical therapeutic potential in the management of neuropathic pain.…”
Section: Discussionsupporting
confidence: 76%
“…Increased levels of B 1 and B 2 receptor mRNA or protein have been found in dorsal root ganglia (DRGs) after sciatic nerve constriction in rats and mice (Petersen et al, 1998;Eckert et al, 1999;Levy and Zochodne, 2000;Yamaguchi-Sase et al, 2003;Rashid et al, 2004). Of note, the systemic administration of B 1 or B 2 receptor antagonists has been found to reduce thermal hyperalgesia and mechanical allodynia produced by sciatic nerve constriction in rats (Levy and Zochodne, 2000;Yamaguchi-Sase et al, 2003;Gougat et al, 2004). Plasma seems to be the main source of endogenous kinins after nerve injury, and there is recent evidence demonstrated that neuropathic pain is reduced in mutant plasma kininogen-deficient B/N-Katholiek rats when compared with normal B/N-Kitasato rats (Yamaguchi-Sase et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The doses of the R-715 and SSR240612 were selected on the basis of literature data or pilot experiments (Gobeil et al, 1996;Fernandes et al, 2003;Gougat et al, 2004). Under these protocols of treatment, neither the R-715 nor the SSR240612 altered the basal threshold response of animals.…”
Section: Tail Withdrawal Response Induced By Thermal Stimulus (Tail Fmentioning
confidence: 99%
“…, 300 mg/kg kindly provided by J. Gougat, Sanofi, Montpellier, France) (Gougat et al, 2004), 5 minutes before the onset of ischemia.…”
Section: Methodsmentioning
confidence: 99%